In Vitro–In Vivo Correlation Strategy Applied to an Immediate‐Release Solid Oral Dosage Form with a Biopharmaceutical Classification System IV Compound Case Study. Issue 7 (2nd June 2014) - Bredael, Gerard M.; Bowers, Niya; Boulineau, Fabien; Hahn, David
<x xml:space="preserve">Abstract</x> The ability to predict in vivo response of an oral dosage form based on an in vitro technique has been a sought after goal of the pharmaceutical scientist. Dissolution testing that demonstrates discrimination to various critical formulations or process attributes provides a sensitive quality check that may be representative or may be overpredictive of potential in vivo changes. Dissolution methodology with an established in vitro–in vivo relationship or correlation may provide the desired in vivo predictability. To establish this in vitro–in vivo link, a clinical study must be performed. In this article, recommendations are given in the selection of batches for the clinical study followed by potential outcome scenarios. The investigation of a Level C in vitro–in vivo correlation (IVIVC), which is the most common correlation for immediate‐release oral dosage forms, is presented. Lastly, an IVIVC case study involving a biopharmaceutical classification system class IV compound is presented encompassing this strategy and techniques. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2125–2130, 2014